Bologna Process and the Professional Education of Lawyers - Mangora, Volodymyr (Pedagogical Discourse, 2013)
The article considers the effect of Bologna Process on the professional education of lawyers in Ukraine aimed at improvement of it quality and effectiveness. Legal maintenance of implementation of Bologna Process in Ukraine is characterized. The ways of improvement of the professional education of lawyers are defined. The necessity of acceptance of legal educational standards in accordance with European standards, transition into double leveled system: a Bachelor, a Master is argued. On the basis of analysis, that took place, the conclusion that higher legal education needs reforms according with the demands of Bologna Process can be done.